Agricultural impact of climate change: A general equilibrium analysis with special reference to Southeast Asia - Fan Zhai; Juzhong Zhuang (Asian Development Bank Institute (ADBI), 2009)
Capitalizing on the most recent worldwide estimates of the impacts of climate change on agricultural production, this paper assesses the economic effects of climate change for Southeast Asian countries through 2080. The results suggest that the aggregate impacts of agricultural damages caused by climate change on the global economy are moderate. However, the uneven distribution of productivity losses across global regions would bring significant structural adjustments in worldwide agricultural production and trade, ultimately leaving the developing world as a net loser. With the anticipated declining agricultural share in the economy, a reduction in agricultural productivity would have small, but non-negligible negative impacts on Southeast Asia's economic output. However, the expected increase of crop import dependence in the coming decades would make most Southeast Asian economies suffer more welfare losses through deteriorated terms of trade. Depending on a country's economic structure, the negative effects are expected to be less for Singapore and Malaysia, but greater for Philippines, Indonesia, Thailand, and Viet Nam. For Southeast Asia to cope with the potential agricultural damages arising from the expected changes in climate the region must concentrate on reversing its current trend of declining agricultural productivity.
Keywords: D58; C68; Q54; Q1; 330